Una mirada sociológica al desempleo - Rubio Arribas, Francisco Javier (Nómadas. Critical Journal of Social and Juridical Science, 2012)
From a sociological´s pointview, the unemployed are a heterogeneous group with significant individual differences in their reactions to the lack of a job. Joblessness has become a major problem for the citizen of this country. The current economic crisis is impacting negatively on employment (dramatic increase in the number of unemployed) and generating long-term unemployed people in areas that had not suffered from this phenomenon before. On the other side, the number of people is increasing with welfare benefits, creating an increased risk of social exclusion. Finally, the current Labour Reform is changing the face of the labor market in our country.
Keywords: unemployment; employment; depression economic; immigration; new profiles unemployed.